A New Strategy to Reduce Toxicity of Ethidium Bromide by Alternating Anions: New Derivatives with Excellent Optical Performances, Convenient Synthesis, and Low Toxicity. Issue 3 (31st January 2020) - Song, Yuchen; Xu, Lei; Wu, Qiong; Xiao, Saiyu; Zeng, Haixiang; Gong, Yanbin; Li, Conggang; Cheng, Sixue; Li, Qianqian; Zhang, Liyao; Li, Zhen
Abstract: The potential threats of ethidium bromide to laboratory staff have drawn more and more attention. Considering that commercial available substitutes still cannot replace ethidium bromide due to some drawbacks, it can be a better solution by functionalizing directly on ethidium bromide moiety. In this work, ethidium bromide is ameliorated via changing the bromide anion into moieties with more twist structures to prevent the aggregation caused quenching in aggregations, and increase more hydrophobic ability to form nanoparticles in aqueous. The nanoparticles of these probes show negative zeta potential, low toxicity, good photostability, and high sensitivity, both in solution tests and gel electrophoresis experiments. Meanwhile, the weak penetration ability through skin constitutes a dual protection for users. Furthermore, the one step synthesis from commercial available ethidium bromide and the convenient purification also do help to these probes in applications. Abstract : Ethidium bromide is ameliorated via changing the anions into moieties with twist structures to prevent from aggregation caused quenching and to form nanoparticles. The nanoparticles show negative zeta potential, low toxicity, good photostability and high sensitivity. The weak penetration ability through skin constitutes a dual protection for users. Furthermore, the brief synthesis and purification also do help to future applications.